Remunerativeness led acreage response of arecanut in Karnataka state - Patil, Kiran Kumar R.; Patil, B.L.; Manjunatha, G.R.; Aditya, K.S. (Journal of Plantation Crops, 2014)
The decision of farmers regarding allocation of farm resources, in general, and land resource which have supply inelasticity is crucial. This decision of farmers in case of commercial plantation crops will be highly influenced by the policies and programmes formulated by the government. The formulated developmental programmes mainly aim at increasing the overall production of the economy and its success depends on the reactions of farmers to such programmes. The increased production can be achieved either through extensive or intensive cultivation or the mix of two. In this context it becomes imperative to have a better insight about the farmers’ response to various price and non-price factors. To understand the behavioural mechanism of arecanut growers in major areca growing districts of Karnataka, Nerlovian lagged adjustment model was employed. The result revealed that it is the expected price (remunerativeness) which has resulted in extensive cultivation in most of the areca growing belts. The result was contrasting in case of Dakshina Kannada where the response of farmers to expected price was negative, which might be due to the fact that growers in this region have shifted to alternative crop i.e., rubber, which is equally remunerative due to wide prevalence of yellow leaf disease. The other likely reason would be the limitation of area for further expansion, since area expansion has met its saturation in the locality. To prove the remunerativeness of arecanut enterprise, representative district Shimoga was chosen. The economics of arecanut cultivation revealed that it is remunerative compared to other major crops of the study area.